WALTER SCOTT - A FOUNDER OF A GENRE OF A HISTORICAL NOVEL IN ENGLISH LITERATURE - Roza Eshbaeva Rustam qizi ,; Khamitov Eldor Erkinovich , (TADQIQOTLAR.UZ, 2024)
This chapter delves into Walter Scott's influence on the historical novel genre. Scott transformed the novel into a contemporary epic by infusing it with national themes, achieved through its historical elements. This approach lent the novel a sense of scholarly significance associated with history, particularly in Scotland during the Enlightenment era. Throughout the nineteenth century, the historical novel became the predominant form of the genre, maintaining its popularity and prestige long after Victorian writers adopted Scott's techniques. Scott's fusion of history and Bildungsroman, as seen in "Waverley; or, 'Tis Sixty Years Since" (1814), served as a model for aspiring national literatures across Europe, its imperial borders, and colonial territories well into the following century.